2006
DOI: 10.1007/s10126-005-6160-4
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and Characterization of a 30.7-kDa Protein from Bacillus licheniformis Associated with Inhibitory Activity Against Methicillin-Resistant Staphylococcus aureus, Vancomycin-Resistant Enterococci, and Listeria monocytogenes

Abstract: Of 131 bacterial isolates from seaweed, a culture of Bacillus licheniformis produced a novel protein with antibacterial activity against methicillin-resistant Staphylococcus aureus, vancomycin-resistant enterococci, and Listeria monocytogenes. The antibacterial activity was maximal in cultures prepared in Columbia broth containing pieces of synthetic polyurethane sponge and shaken at 210 to 230 rpm. Antibacterial activity was not found in cultures grown statically or with different speeds of rotary shaking. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
0
16
1
Order By: Relevance
“…Stein (2005) reported wild type of B. subtilis has amazing properties of producing more than two dozens of antibiotics. It has already been demonstrated that the antimicrobial compound produced by B. licheniformis culture was effective against methicillin-resistant S. aureus strain MRSA9551 and vancomycin-resistant Enterococcus strain (Jamal et al, 2006). But in the present study such activity was not observed against S. aureus with GM5 strain (B. licheniformis).…”
Section: Discussioncontrasting
confidence: 79%
“…Stein (2005) reported wild type of B. subtilis has amazing properties of producing more than two dozens of antibiotics. It has already been demonstrated that the antimicrobial compound produced by B. licheniformis culture was effective against methicillin-resistant S. aureus strain MRSA9551 and vancomycin-resistant Enterococcus strain (Jamal et al, 2006). But in the present study such activity was not observed against S. aureus with GM5 strain (B. licheniformis).…”
Section: Discussioncontrasting
confidence: 79%
“…are well recognized as bacteriocin producers [6], no other bacteriocins have been isolated from marine-derived Bacillus , to date, with the exception of one from a B. cereus strain of fish origin [23]. Others produced by B. licheniformis strains of fish [24] and seaweed [25] origin can only be referred to as bacteriocin-like, due to a lack of characterization. …”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial activity range of LanA is rather narrow and limited to Gram-positive bacteria such as B. subtilis, B. smithii, B. megaterium, K. gibsonii, Staphylococcus and Streptococcus sp. But in earlier reports B. licheniformis produced a novel protein (30.7 kDa) with antibacterial activity against methicillin-resistant S. aureus, vancomycin-resistant Enterococci and L. monocytogenes (Jamal et al 2006). Martirani et al (2002) reported that bacillocin 490 is active principally against species phylogenetically related organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial peptides or lantibiotic bacteriocins are produced by many gram positive bacteria including B. subtilis, B. thuringiensis, B. stearothermophilus (Sharp et al 1979), B. licheniformis (Jamal et al 2006), B. megaterium (Kiss et al 2008), B. thermoleovorans (Novotny and Perry 1992), B. cereus (Bizani et al 2008) and B. coagulans (Hyronimus et al 1998). Several of the above mentioned bacteriocins were not purified to homogeneity for the study of biochemical characterizations and genetic information on these peptides are limited.…”
Section: Introductionmentioning
confidence: 99%